Intralesional injection of biosimilar rituximab in recalcitrant mucocutaneous lesions of patients with pemphigus vulgaris: A pilot study. Issue 6 (30th October 2020) - Mazloom, Ebrahim; Daneshpazhooh, Maryam; Shokouhi Shoormasti, Raheleh; Balighi, Kamran; Mahmoudi, Hamidreza; Moradi Ketisari, Masoud; Eslami Faresani, Vahid; Ghandi, Narges
Abstract: The efficacy of intravenous rituximab (RTX) in patients with pemphigus have been shown in the previous studies. The study aimed to investigate the effectiveness of intralesional injection of RTX in the healing of pemphigus lesions, with lower doses and probable better safety profile than intravenous RTX. Eleven Pemphigus patients with recalcitrant lesions received two intralesional injections of biosimilar RTX, 5 mg/cm 2 . During 6 months follow‐up, Pemphigus Disease Area Index, the patients' satisfaction, quality of life, the disease activity, the number and size of lesions, the anti‐desmoglein (Dsg) 1 and 3 antibodies and the count of CD4+ and CD19+ cells were assessed. All patients were in partial remission on therapy. The absolute count of CD19+ B cells showed a statistically significant decline ( P = .006). The percentage of CD4 + T lymphocytes increased 2 weeks after injection and decreased 2 weeks later ( P = .01). The average number and size of lesions decreased. The concentration of anti‐Dsg 3 antibody decreased insignificantly during the study. The severe pain during the injection was considered as the main complication. At the end of the study, two patients were in complete remission on therapy, and the other nine remained in partial remission on therapy. Few side effects resulting from intralesional injection of RTX and enhanced quality of life of the patients were considered as the valuable achievements of this study. The results showed that although a low dose of RTX leads to a significant decrease of CD19+ B lymphocytes, it did not show parallel clinical effectiveness.